2011
DOI: 10.1002/jpln.201000325
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐use efficiency traits of mini‐watermelon in response to grafting and nitrogen‐fertilization doses

Abstract: Two experiments were conducted to study the effect of grafting on nitrogen-use efficiency (NUE) in mini-watermelon plants. In the first study, mini-watermelon plants (Citrullus lanatus [Thumb.] Matsum. and Nakai cv. Minirossa) either ungrafted or grafted onto Macis, Vita (Lagenaria siceraria [Mol.] Standl.), PS1313, and RP15 (Cucurbita maxima Duchesne × Cucurbita moschata Duchesne) rootstocks grown in hydroponics were compared in terms of shoot dry biomass, leaf area, root-to-shoot ratio, SPAD index, shoot N u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 48 publications
8
52
1
3
Order By: Relevance
“…The period of greatest absorption of N was 32-60 DAT for 'Precious Petite' and 20-70 DAT for BGCIA 941, when N reached 15 g plant -1 and 20.9 g plant -1 , respectively. The highest increase in nitrogen observed for 'Precious Petite' grafted onto Line BGCIA 941 was similar to that found by Colla et al (2011), for 'Minirossa' watermelon grafted onto different rootstocks.…”
Section: Source Of Variationsupporting
confidence: 83%
“…The period of greatest absorption of N was 32-60 DAT for 'Precious Petite' and 20-70 DAT for BGCIA 941, when N reached 15 g plant -1 and 20.9 g plant -1 , respectively. The highest increase in nitrogen observed for 'Precious Petite' grafted onto Line BGCIA 941 was similar to that found by Colla et al (2011), for 'Minirossa' watermelon grafted onto different rootstocks.…”
Section: Source Of Variationsupporting
confidence: 83%
“…Previous studies revealed that the grain yield and nitrogen usage efficiency was significantly related to enzyme activities. In the present study, the balanced fertilisation increased the Vmax value of soil dehydrogenase, a finding that is consistent with reported results (Colla et al, 2011;Sun et al, 2012). Based on the IFI values, the combination of organic and inorganic fertilisation is the best method to improve soil fertility.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned above, to achieve high crop yields, large amounts of NO 3 fertiliser are still required. However, to achieve even higher yields, an overproportional higher and therefore more inefficient input of NO 3 fertiliser is needed (Hirel et al 2007;Colla et al 2011). Results from Experiment one, which used two nitrogen concentrations, support the conclusion that rather than using very high amounts of NO 3 fertiliser, it may be worth investigating the interactions between NO 3 , IAA/IAA PAT CKs, and gibberellins in detail, which may ultimately show how to reduce the amount of NO 3 fertiliser while still obtaining high yields.…”
Section: Discussionmentioning
confidence: 99%